Dados pessoais sob vigilância: repercussões do caso Cambridge Analytica X Facebook - França, Joelma da Silva Machado de (2021)
It is no longer possible to conceive society, politics and democracy ignoring the imminent risks about the extinction of the right to privacy, in this time, resigned in the right to data protection. The expansion of surveillance applied in the daily life of citizens, especially in face of the advent of the Internet of Things, has forced the law to take a new look at categories such as identity, personality, regarding the intertwining of the digital sphere with the real sphere, where personal data has reached a high market value. Such reality is also evidenced by the new data protection law in Brazil (Law 13.709/2018). The Cambridge Analytica X Facebook case clarifies about the ways in which such informational business operates, where the manipulation of humans through the operation of algorithms was intended. Thus, certain public and private actors act in affront to the dignity of the human person, with antidemocratic practices that reinvent themselves in the face of the technological apparatus, and it is not possible to know in full how such power will manifest itself in the future. The main purpose of this paper is to analyze to what extent the surveillance operated by the technological apparatus of global reach will or will not be able to exert some kind of control over global society, based on the Cambridge Analytica X Facebook case (2016). The methodology employed in this research is the deductive method. The method of procedure chosen for the research was the case study. Regarding writing techniques, use was made of summaries and fiches. The basic theory adopted conjugates authors such as Zygmunt Bauman, Stefano Rodotà, and Bruno Ricardo Bioni in dialogue with other authors. The intertwining of surveillance with the technological apparatus has made possible the construction of a global system that operates the manipulation of the few over the multitude of human beings.